Description Of The Levels Of Physical Activity and Eating Pattern of New Students In Medicine Education Program Faculty Of Medicine Udayana University During The Covid-19 Pandemic - Dharmajaputra, Gede Bagus; Ani, Luh Seri; Duarsa, Dyah Pradnyaparamita (E-Jurnal Medika Udayana; Vol 13 No 10 (2024): E-Jurnal Medika Udayana, 2024)
The Covid-19 pandemic has made many people change their lifestyle where time spent at home causes productivity to decrease and desire to increase. Decreased physical activity and increased eating patterns cause changes in nutritional status. Many have experienced a change in their diet due to the need to maintain their immunity, not shopping outside the home, and cooking a lot for themselves. The purpose of this study was to describe the level of physical activity and eating patterns of new students in the Medical Education Study Program, Faculty of Medicine, Udayana University during the Covid-19 pandemic. This study used a quantitative descriptive method in a cross-sectional way. The sample of this research is Udayana University Medical Education Students class of 2021 who meet the criteria. A total of 73 students met the sample requirements and were selected using the free random sample method which was calculated using the Lemeshow formula. Data were collected using a questionnaire method, namely age, sex, area of ??origin, area of ??residence, weight, height, nutritional status, level of physical activity, and eating patterns. The results of the study were that the majority were female, namely 61 people (64%) and men as many as 35 people (36%). The highest number of respondents aged 18 years was 54 people (56%). BMI categories normal (70%), underweight (8%), overweight (19%), obesity (3%). Light activity (42%), moderate activity (34%), vigorous activity (24). Student eating patterns during a pandemic vary in type, amount, frequency. Adequacy of energy, protein, fat, carbohydrates 35% is above average. The proportion of BMI and physical activity of students in terms of age and gender is dominated by the normal category and students with normal BMI have moderate physical activity. The conclusion of this study was that most of the light activities were carried out during the pandemic with varied meal frequencies and above average nutritional adequacy. Keywords : Physical activity, Diet, Covid-19 Pandemic